Performance of UK Distribution Networks with single-phase PV systems under fault. (December 2019) - Bhagavathy, Sivapriya; Pearsall, Nicola; Putrus, Ghanim; Walker, Sara
Highlights: Development of a generic dynamic PV model including under/over voltage protection. Analysis of the impact of fault on the performance of single-phase PV systems. Analysis of the impact of PV systems on the dynamic performance of DN. Implications of the adoption of different standards on unwanted tripping of PV systems. Analysis of the impact of PV systems on the protective mechanisms in DN. Abstract: Faults are a major concern to the dynamic performance of distribution networks. With the predicted increase in PV contribution, it is vital to understand the impact of PV on the distribution network. However, there is very little work published that address the impact of PV systems on the dynamic performance of distribution networks. Most PV systems connected at the distribution level are single-phase in nature. A generic single-phase dynamic PV model, including the protection mechanism, is presented in this paper. This enables the evaluation of the dynamic performance of distribution networks with multiple single-phase PV systems. The paper analyses the impact of faults on the PV inverter output using the models developed. The impact of PV on the network performance during fault is then analysed. The implications of the adoption of different regulations, viz. G-83, IEEE 1547:2018, IEC 61727 and VDE 0126-1-1, are also discussed. The results show that the presence of PV systems does not significantly affect the performance of the distribution network during faults. Also, the usual concern of loss of protection co-ordination does not occur at this voltage level. Faults that are far from the PV terminals would be cleared within 0.2 s. This indicates that the disconnection delay of 0.5 s as stipulated by G-83 is appropriate. However, a lower cut-off voltage for under-voltage disconnection than the current value stipulated in G-83 would enable more PV systems to stay connected during fault and avoid unnecessary loss of generation. The network used in this work is a representative of distribution networks and protection schemes in the UK. The results of this analysis are therefore extendable to any radial distribution network that uses standard protection, e.g. fuses and relays in low voltage distribution networks.